Ammonium reduces oxalate accumulation in different spinach (Spinacia oleracea L.) genotypes by inhibiting root uptake of nitrate. (1st November 2015) - Liu, Xiaoxia; Lu, Lingli; Chen, Qiuhui; Ding, Wenya; Dai, Peibin; Hu, Yan; Yu, Yan; Jin, Chongwei; Lin, Xianyong
Highlights: Leaf oxalate accumulation is associated with uptake of nitrate but not ammonium. Addition of ammonium reduced nitrate uptake and leaf oxalate accumulation. Ammonium reduces spinach oxalate content by inhibiting nitrate uptake. Abstract: Excessive accumulation of oxalate negatively affects nutritional value of many vegetables, such as spinach ( Spinacia oleracea L.). Mixed solution of ammonium and nitrate could effectively reduce oxalate accumulation, while the mechanism involved remains unknown. High (Heizhenzhu) and low (Weilv) oxalate-accumulated spinach genotypes were used in this study to investigate the association of oxalate accumulation and root uptake of nitrogen. Exposure of increasing nitrate or mixed-nitrogen (nitrate:ammonium = 1:1) significantly increased leaf total and soluble oxalate contents. In contrast, increasing ammonium did not result in elevation of leaf oxalate. Correlation analysis confirmed that leaf oxalate accumulation was positively associated with root uptake of nitrate but not ammonium. Moreover, addition of ammonium significantly reduced nitrate uptake rate, and subsequently decreased leaf oxalate accumulation. The results suggest that oxalate synthesis in spinach leaves is associated with its root uptake of nitrate, and ammonium is able to reduce oxalate accumulation by inhibiting uptake of nitrate.